PENGARUH PENERAPAN TEKNIK BISNIS BERESIKO TERHADAP HASIL BELAJAR BIOLOGI KELAS IX SMAN 1 KOTO BARU KABUPATEN DHARMASRAYA - Inggraini, Frisilia; Sudirman, Sudirman; Maizeli, Annika (Pendidikan Biologi, 2013)
ABSTRACTÂ Â This research is motivated by the study is still dominated by the teacher, only a few students pay Â attention to the teacherâs explanation. Besides, some of them are not motivated and less interested in participating in the learning process. Most of them enjoy with their own activities. In this case, the avarage of mid term student in the academic year 2010/2011 and 2011/2012 is under KKM (75) for reproductive system. The purpose of this research is to know the influence of application by Using Business Technique get at risk Towards The Biology Achievement for The XI students in SMAN 1 Koto Baru regency of Dharmasraya. The Kind of this research is experiment. By using Randomized Cantrol Group Postest Only Design. The population in this research is the whole students of XI science who register for second semester in SMAN 1 Koto Baru in the academic yearÂ  Â 2012/2013. The test used in Objective test with a reliability test isÂ Â Â Â Â Â  Â =0,92. Techniques of data analysis used the test (t). Based on the analysis of data found that the two classes are normally distributed and homogenous samples. Theresult of hypothesis test obtainedÂ Â Â Â Â Â Â Â Â Â  Â the level of confidence 95% = (Î± = 0,05)is 1,67 and Â = 11,27 it means Â >Â Â Â Â Â Â Â Â Â Â  Â Therefore, the hypothesis in this research is received. Based on the hypothesis, the writer conclude that the influence Â of Â application Â by Â using Â business Â technique Â get Â at Â risk Â towards Â the biology Â achievement Â for Â the Â XI Â student Â in Â SMAN Â 1 Â Koto Â Baru Â regencyÂ  of Dharmasraya.Â Â Â